Penambahan Berbagai Dosis Ekstrak Buah Merah (Pandanus conoideus) pada Air Minum terhadap Produktivitas Ayam Kampung Joper: Supplementation Various Dose of Red Fruit (Pandanus conoideus) in Drinking Water on Productivity of Joper Local Chicken (Jurnal Agroekoteknologi dan Agribisnis, 2022)
The use of antibiotics in animal feed can leave residues that are harmful to health, therefore a solution is needed to replace the use of antibiotics, namely phytobiotics. This study aims to determine the effect of giving red fruit oil phytobiotics on body weight and drinking water consumption of joper native chicken that was given phytobiotic nanoencapsulated red fruit oil (Pandanus conoideus) which was applied in drinking water as an ingredient to increase productivity of joper native chicken. This study used RAL pattern in the same direction with 5 treatments and 4 replications. Each replication consisted of 2 animals as experimental unit, treatment consisted of negative control (P0), 1,25% red fruit oil (P1), 2.5% phytobiotic nanoencapsulated red fruit oil (P2), 3.75% phytobiotic nanoencapsulated oil. red fruit (P3), and 5% phytobiotic nanoencapsulated red fruit oil (P4). The results of this study can increase the average body weight of chickens and drinking water consumption for P0, P1, P2, P3 and P4 respectively 0.700 kg; 0.825 kg; 1.025 kg; 1.125 kg; and 1,225 kg and 5,900 ml; 4,880 ml; 5,700 ml; 5,720 ml and 6,220 ml. Based on the results of data analysis, the addition of 5% red fruit oil (P4) nanoencapsulated phytobiotics by water intake was the best treatment in terms of growth in body weight of chickens and drinking water consumption. Based on the results of the study, it can be concluded that the addition of red fruit oil using nanoencapsulated phytobiotic technology is proven to increase the productivity of joper native chickens.